2012
DOI: 10.4141/cjps2011-249
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of glyphosate-resistant giant ragweed (Ambrosia trifida L.) in southwestern Ontario

Abstract: Vink, J. P., Soltani, N., Robinson, D. E., Tardif, F. J., Lawton, M. B. and Sikkema, P. H. 2012. Occurrence and distribution of glyphosate-resistant giant ragweed ( Ambrosia trifida L.) in southwestern Ontario. Can. J. Plant Sci. 92: 533–539. Giant ragweed is the first confirmed glyphosate-resistant (GR) weed in Canada. A survey was conducted to document the distribution of GR giant ragweed in southwestern Ontario. Giant ragweed seed was collected from 102 sites in Essex (70), Chatham-Kent (21), Lambton (10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…Subsequently, resistance to glyphosate was confirmed at 3 and 12 times the maximum recommended rate under greenhouse and field testing, respectively. In 2009 and 2010, a survey of southwestern Ontario confirmed GR giant ragweed populations in 47 additional locations indicating a greater distribution of resistant plants than originally anticipated [10]. By 2012, GR giant ragweed was further detected in four Ontario counties, with five populations demonstrating multiple resistances to both glyphosate and cloransulam-methyl [11].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Subsequently, resistance to glyphosate was confirmed at 3 and 12 times the maximum recommended rate under greenhouse and field testing, respectively. In 2009 and 2010, a survey of southwestern Ontario confirmed GR giant ragweed populations in 47 additional locations indicating a greater distribution of resistant plants than originally anticipated [10]. By 2012, GR giant ragweed was further detected in four Ontario counties, with five populations demonstrating multiple resistances to both glyphosate and cloransulam-methyl [11].…”
Section: Introductionmentioning
confidence: 89%
“…Giant ragweed populations were confirmed as resistant to glyphosate prior to study establishment [10]. The first set of trials determined GR giant ragweed control using various PP tank-mixtures while the second examined GR giant ragweed control using POST tank-mixes.…”
Section: Study Establishmentmentioning
confidence: 99%
“…Giant ragweed seedlings begin to emerge in early March [10] and continue to emerge until late July [11]. Historically, growers in Ontario would control this problematic weed with glyphosate; however, in 2008 giant ragweed was confirmed to be resistant to glyphosate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dose response curve indicated ≥ 90% control of 10-cm tall giant ragweed even with a lower than the recommended rate (1,640 g ae ha -1 ) at 21DAT (Figure 2A), while the 20-cm tall giant ragweed was controlled 87 to 93% at the recommended rate at 21 DAT. Similarly, Vink et al (2012) reported > 90% control of 2-to 17-cm tall giant ragweed with 2,4-D ester (500 g ae ha -1 ) applied alone, indicating the sensitivity of giant ragweed to 2,4-D. Higher level of giant ragweed control has been reported in a previous study despite the plant height being higher than recommended. For example, Robinson et al (2012) reported ≥ 99% control of 26-to 46-cm tall giant ragweed with 2,4-D (280 g ae ha -1 ) applied alone or tank-mixed with glyphosate (1,120 g ae ha -1 ).…”
Section: Giant Ragweedmentioning
confidence: 81%
“…Results of this study suggested that Enlist Duo™ herbicide is very effective for controlling glyphosate-resistant giant ragweed. This might be due to giant ragweed's sensitivity to phenoxy herbicides Vink et al, 2012). Recently, Kaur et al (2014) and Jhala et al (2014a) reported 99% control of glyphosate-resistant giant ragweed in Nebraska with herbicide programs that included preplant application of 2,4-D in soybean.…”
Section: Giant Ragweedmentioning
confidence: 99%